Pengembangan Bahan Ajar Nahwu Berbasis Kontrastif Untuk Mengatasi Interferensi Bahasa Indonesia Terhadap Bahasa Arab - Afif Kholisun Nashoih; M. Faridl Darmawan (Arabiyatuna : Jurnal Bahasa Arab, 2019)
This research is motivated by the many contents of the elements of Indonesian interference in Insha 'students of the Arabic Language Education University of KH. A. Wahab Hasbullah. The interference is caused by the lack of students' understanding of syntax rules. Therefore, the purpose of this research is to develop Arabic syntax teaching materials as a solution to overcome Indonesian interference with Arabic. The method used in this research is R&D by adopting the ADDIE development model (analysis, design, develop, implementation, evaluation). This research produces Arabic syntactic teaching material which is presented through a comparison between the rules of Arabic and Indonesian, and contains material that emphasizes the aspect of function, which includes the material formation of sentences as well as variations and complement. After going through the validation stage with a very valid qualification of 89.1%, the results of the data analysis state that the developed teaching material is able to improve the learning outcomes of students in the course of nahwu (Arabic syntax) which certainly goes hand in hand with increasing their understanding. This increase has a significant effect as a solution to minimize the level of interference. This is proven through further analysis by comparing the results of the pretest which reached an average of 57.26% and the posttest which reached an average of 79.03% so that it can be interpreted that grammatical errors due to interference factors can be overcome.